Regulation of Chk1 Kinase by Autoinhibition and ATR-mediated Phosphorylation - Katsuragi, Yoshinori (The American Society for Cell Biology, 2004)
The checkpoint kinase Chk1 undergoes ATR-mediated phosphorylation and activation in response to unreplicated DNA, but the precise mechanism of Chk1 activation is not known. In this study, we have analyzed the domain structure of Xenopus Chk1 and explored the mechanism of its activation by ATR-mediated phosphorylation. We show that the C-terminal region of Xenopus Chk1 contains an autoinhibitory region (AIR), which largely overlaps with a bipartite, unusually long (∼85-amino acid) nuclear localization signal. When coexpressed in oocytes or embryos, the AIR can interact with and inhibit the kinase domain of Chk1, but not full-length Chk1, suggesting an autoinhibitory intramolecular interaction in the Chk1 molecule. If linked with the preceding ATR phosphorylation domain that has either phospho-mimic mutation or genuine phosphorylation, however, the AIR can no longer interact with or inhibit the kinase domain, suggesting a conformational change of the AIR by ATR-mediated phosphorylation. Even in full-length Chk1, such phospho-mimic mutation can interfere with the autoinhibitory intramolecular interaction, but only if this interaction is somewhat weakened by an additional mutation in the AIR. These results provide significant insights into the mechanism of Chk1 activation at the DNA replication checkpoint.